2018
DOI: 10.1042/cs20180306
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and inflammation: overview and updates

Abstract: The concept that inflammation participates pivotally in the pathogenesis of atherosclerosis and its complications has gained considerable attention, but has not yet entered clinical practice. Experimental work has elucidated molecular and cellular pathways of inflammation that promote atherosclerosis. The recognition of atherogenesis as an active process rather than a cholesterol storage disease or a repository of calcium has highlighted some key inflammatory mechanisms. For example, mononuclear phagocytes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
438
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(459 citation statements)
references
References 58 publications
8
438
0
13
Order By: Relevance
“…Inflammation is considered a main process involved in atherosclerosis development [74]. A recent meta-analysis of nine RCTs and 509 patients showed that the CoQ 10 supplementation in chronic inflammatory diseases (60-500 mg/day for 8-12 weeks) is responsible for the significant reduction in the plasma levels of tumor necrosis factor alpha (TNF-α) (SMD: −0.44, 95% CI: (−0.81 to −0.07) mg/dl; I 2 = 66.1%, p < 0.01) and in IL-6 levels (SMD: −0.37, 95% CI: (−0.65 to −0.09), p = 0.01) [75].…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Inflammation is considered a main process involved in atherosclerosis development [74]. A recent meta-analysis of nine RCTs and 509 patients showed that the CoQ 10 supplementation in chronic inflammatory diseases (60-500 mg/day for 8-12 weeks) is responsible for the significant reduction in the plasma levels of tumor necrosis factor alpha (TNF-α) (SMD: −0.44, 95% CI: (−0.81 to −0.07) mg/dl; I 2 = 66.1%, p < 0.01) and in IL-6 levels (SMD: −0.37, 95% CI: (−0.65 to −0.09), p = 0.01) [75].…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Therefore, we conducted this study and found that both before and after adjustment by age/gender, lncRNA THRIL was greatly enhanced in CHD patients compared to controls, and it showed good predictive value for increased CHD risk. These data could be explained by that: (a) LncRNA THRIL might regulate several pathways (such as TNF‐α and NF‐κB) to induce inflammation as in systemic lupus erythematosus model and osteoarthritis model, which accelerated the process of atherosclerosis and rose the possibility of CHD incidence; (b) it is proposed that lncRNA THRIL activated TNF‐α transcription, and TNF‐α is a major cause of local and systemic insulin resistance . Thus, it was possible that lncRNA THRIL might up‐regulate TNF‐α to increase the risk of diabetes mellitus, one of the risk factors of CHD, thereby enhanced the incidence of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids, levels of which were significantly elevated in the PWV-High group, have been suggested to be atherogenic through induction of endothelial dysfunction [58,59]. Numerous reports have indicated increased oxidative stress and chronic inflammation in patients with atherosclerosis [60][61][62][63]. Inflammatory cytokines (TNF, IL-6, IL-1), which contribute to inflammatory responses, have been reported to promote osteoclast differentiation [64][65][66][67], and oxidative stress was shown to inhibit osteogenic bone formation and differentiation maturation [21].…”
Section: Discussionmentioning
confidence: 99%